(3GdCMcGe hTDhfgG hCWhGQgGs - (3GdfLaj, Ydj Hf eMeO QVG cGTa GdZWGA, J (B1350(3g`s ((3HNW GdeDdas)
(3ChdgG (B:s
(3CbSGe GdMce GdTQYjs
(3BNQgG (B:s
(3hEPG de jbe GdOdjd Ydi UMJg adG jcJai Hg dYOe GdeDef ef GdYbhHI dh cGf eNGdaG ddhGbYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B: (3L(B2(3, U (B504s
(3GdCYdGe(B: (3L(B5(3, U(B19s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3CUhd Gdabgs